2016
DOI: 10.1186/s13019-016-0510-3
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of outcomes with intramedullary fixation of fractured ribs

Abstract: BackgroundSurgical management of fractured ribs with internal fixation is an increasingly accepted therapy. Concurrently, specific rib fixation prostheses are being developed which should improve results and minimise hardware and rib/splint construct failures. The Synthes titanium intramedullary splint lends itself to difficult to access areas such as posterior rib fractures and fractures under the scapula. We analyse a case series of patients in whom this rib fixation prosthesis has been used.MethodsFifteen p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 16 publications
(22 reference statements)
0
14
0
3
Order By: Relevance
“…By 6 months, all rib fractures were completely healed. This small retrospective review demonstrated that while fracture healing may be delayed on CT-imaging, functional recovery is comparable to cortical plating [39] .…”
Section: Standard Posterolateral Thoracotomymentioning
confidence: 88%
“…By 6 months, all rib fractures were completely healed. This small retrospective review demonstrated that while fracture healing may be delayed on CT-imaging, functional recovery is comparable to cortical plating [39] .…”
Section: Standard Posterolateral Thoracotomymentioning
confidence: 88%
“…Extracortical plating provided superior fracture stabilization compared to intramedullary rib splinting as intramedullary splinting has been shown to fail in vitro and in vivo secondary to cortical bone perforation and fracture line instability. [7] Extracortical rib plating provides proximal and distal fixation not afforded by intramedullary splinting. OWT approach may serve as a viable option for external posterior rib fixation in future chest wall reconstruction.…”
Section: Discussionmentioning
confidence: 99%
“…This feature is theoretically attractive when a minimally invasive approach is contemplated, or difficult to expose fracture sites (e.g., posterior, subscapular) are addressed. Preliminary data suggest adequate healing using splints, although much more research is needed (42). Concerns have been raised in the literature by some investigators that the single point of fixation may allow distraction (separation of the bone) at the fracture site (7).…”
Section: Mode Of Fixationmentioning
confidence: 99%